Biofunctionalization Effectiveness of Titanium Oxide Thin Films Obtained with Physical and Chemical Vapour Deposition Methods for Optical Label-free Biosensing Applications. (2017) - Dominik, M.; Roźniecka, E.; Wachnicki, Ł.; Niedziółka-Jönsson, J.; Godlewski, M.; Bock, W.J.; Śmietana, M.
Abstract: An influence of titanium oxide (TiOx ) deposition method, i.e., chemical (atomic layer deposition, ALD) and physical (reactive magnetron sputtering, RMS) vapor deposition, on the optical properties and surface chemical modification were investigated. TheTiOx film was used as a functional coating for enhancing sensing properties of two types of label-free optical sensors, i.e., localized surface plasmon resonance (LSPR) sensors based on gold nanoparticles and induced in optical fibre long-period gratings (LPGs) working in visible and infrared spectral range, respectively. We have found that independently on deposition method the films increase the sensitivity of LPG and enhance biofunctionalization capabilities.